Analysis of Injury Risk toward Swimming Athletes based on the Result of Functional Movement Screening - Wildan Qohhar; Egiesta Dwi Ariani; Rifki Wahyudin; Asah Iskandar (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
This study aims to analyze the risk of injury in swimming athletes based on the results of Functional Movement Screening (FMS) by considering gender and age group factors. The research method used is a quantitative approach with a descriptive design. The sample in this study consisted of 73 swimming athletes in age groups (KU) 3 and KU 4, aged 10–13 years in Serang City. The sampling technique used was total sampling, so the entire population meeting the criteria was included in this study. The main instrument used is Functional Movement Screening (FMS), which measures the level of stability, mobility, and functional movement quality of athletes as indicators of injury risk. The results showed differences in FMS scores between male and female athletes, where female athletes tended to have lower scores than male athletes, indicating a higher risk of injury. In addition, analysis by age group showed that athletes in the 12–13 years old age group (KU 3) had better average FMS scores compared to athletes aged 10–11 years (KU 4), indicating that with increasing age, the level of movement control and stability increases. These findings underscore the importance of tailored training programs tailored to individual needs, taking into account gender and age, to reduce injury risk in young swimmers.